New Polymeric Admixture for Cement Based on Hyperbranched Poly Amide-Ester with Pentaerythritol Core. (14th May 2013) - Amin Ibrahim, Amal; El-Sayed Abdel-Megied, Ahmed; Sayed Selim, Mohamed; Hassenen Darweesh, Hassan; Mohamed Ayoub, Magdy
Abstract : Hyperbranched poly amide-ester (HBPAE) was synthesized by a solution condensation polymerization through one-step process using pentaerythritol as a central core and AB2 prepolymerized monomer which was rapidly prepared at room temperature (25°C) using commercially available maleic anhydride (MA) and diethanolamine (DEA) monomers in the presence of p-toluene sulfonic acid as a catalyst. The prepared polymer was characterized by GPC, IR, 1 H-NMR, and thermal analysis (TGA and DSC). The influence of the polymer addition to the cement paste was investigated by measuring the effect of 1, 3 and 5 wt% HBPAE solutions on the properties of ordinary portland cement (OPC). Accordingly, several parameters were investigated such as water of consistency, setting times, bulk density, apparent porosity, compressive strength, and combined water content of the polymer/cement pastes. The SEM images proved that the incorporation of HBPAE with the OPC cement did not affect the chemical composition of hydrates, but it only affected the physical state, shape, size, morphology, and crystallinity of the formed hydrates. The results showed that the polymer addition to OPC pastes improved the physicomechanical properties of cement.